Pengaruh Desentralisasi Dan Ketidakpastian Tugas Terhadap Kinerja Manajerial Dengan Sistem Akuntansi Manajemen Sebagai Variabel Intervening: Studi Empiris Pada Industri Percetakan Skala Besar Di Provinsi Banten - HERMAN WIJAYA (Universitas Serang Raya, 2021)
This study aims to test empirically the effect of two contextual variables, namely task uncertainty and decentralization on managerial performance with the Management Accounting System (SAM) as an intervening variable. Besides, this research also examines the effect of each contextual variable with SAM, the effect of SAM on managerial performance either directly or moderated by the two contextual variables.Respondents in this study were functional managers of large-scale printing companies in Banten. The sample used was 100 managerial functional. The analysis tool uses Structural Equational Modeling (SEM) through Partial Least Square (PLS) and Sobel Test.The results show that task uncertainty has a positive and significant effect on managerial performance, decentralization has a positive and significant impact on managerial performance, management accounting systems have a positive and significant impact on managerial performance, task uncertainty has a positive and significant impact on the management accounting system. , decentralization has a positive and significant effect on the management accounting system. The results of the indirect effect test proved that task uncertainty had an effect on managerial performance mediated by the management accounting system. Key word : Task uncertainty, decentralization, management accounting systems, managerial performance